COMMUNITY STRUCTUREECHINODERMATA AT PANDARATAN BEACH PONDOK BATU SUBDISTRICT SARUDIK DISTRICT TAPANULI TENGAH REGENCY - Sihombing, Kelvin; Efriyeldi, Efriyeldi; Zulkifli, Zulkifli (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2019)
ABSTRACT Echinodermata is a thorn-skinned animal and consists of 5 (five) classes namely Asteroidea, Ophiuroidea, Crinoidea, Echinoidea and Holothuroidea. Echinoderms can be found in waters with coral, sand and seagrass substrates. The research was conducted in March to April 2019. The purpose of this study was to determine Echinodermata species found on the coast of Pandaratan and the community structure of Echinoderms which included abundance, relative abundance, diversity, uniformity, dominance, and distribution patterns at each observation station in coastal waters of Pandaratan. The method used in this study is the survey method and the determination of the location of the observation is determined by purposive sampling. The results showed that Echinodermata found at the observation station on the coast of Pandaratan consisted of 3 classes and 4 species, namely Archaster typicus, Diadema setosum, Holothuria atra and Holothuria scabra. The abundance of Echinoderms is in the range of 6.22 - 6.78 ind / m2. Relative abundance of Echinoderms on the coast of the Pandaratan it is estimated that in Archaster typicus species at station I with a percentage of 100%. The distribution pattern of Echinoderms consists of 1 (one) distribution category, namely grouping. Echinodermata diversity index is in the range 0 - 1.7391. The uniformity index has a range of values of 0 - 0.9135 and the dominance index has a range of values of 0.1422 - 1.  Keywords :Echinodermata, Abundance, Relative Abundance, Diversity, Uniformity, Dominance, Distribution Patterns